2020
DOI: 10.1002/iub.2337
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of peroxisome proliferator‐activated receptor‐alpha alleviates myocardial injury in diabetic cardiomyopathy by downregulating 3‐hydroxy‐3‐methylglutaryl‐coenzyme A synthase 2 expression

Abstract: Diabetic cardiomyopathy (DCM) is a cardiac disorder, which affects around 12% diabetic patients, resulting in overt heart death. Our initial bioinformatic analysis identified the differentially expressed gene 3‐hydroxy‐3‐methylglutaryl‐coenzyme A synthase 2 (HMGCS2) in DCM, which may be activated by peroxisome proliferator‐activated receptor‐alpha (PPARα) based on previous evidence. Therefore, the present study aims to explore the effect of PPARα on the development of DCM through regulating HMGCS2. The express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…HMGCS2 is a mitochondrial enzyme that catalyzes the first reaction of ketogenesis and related research has mainly focused on its roles in diabetes, tumor, Alzheimer's disease, and intestinal cell differentiation (Shi et al , 2017 ; Wang et al , 2017 , 2019b , 2020b ; Wan et al , 2018 ; Kim et al , 2019 ; Tomita et al , 2020 ). Increased HMGCS2 expression in diabetes enhanced the production of ketone bodies, thus leading to diabetic cardiomyopathy (Wang et al , 2020a ), whereas the function of HMGCS2 in diabetic nephropathy remains controversial. Tomita et al ( 2020 ) reported that SGLT2 inhibitors promoted ketone body rise through HMGCS2, thereby inhibiting mTORC1 in proximal renal tubules, explaining the protective effect of SGLT2 inhibitors on kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGCS2 is a mitochondrial enzyme that catalyzes the first reaction of ketogenesis and related research has mainly focused on its roles in diabetes, tumor, Alzheimer's disease, and intestinal cell differentiation (Shi et al , 2017 ; Wang et al , 2017 , 2019b , 2020b ; Wan et al , 2018 ; Kim et al , 2019 ; Tomita et al , 2020 ). Increased HMGCS2 expression in diabetes enhanced the production of ketone bodies, thus leading to diabetic cardiomyopathy (Wang et al , 2020a ), whereas the function of HMGCS2 in diabetic nephropathy remains controversial. Tomita et al ( 2020 ) reported that SGLT2 inhibitors promoted ketone body rise through HMGCS2, thereby inhibiting mTORC1 in proximal renal tubules, explaining the protective effect of SGLT2 inhibitors on kidney.…”
Section: Discussionmentioning
confidence: 99%
“…HMGCS2 has been suggested to play important roles in diabetes, tumor, Alzheimer's disease, and intestinal cell differentiation (Wan et al , 2018 , 2019 ; Cheng et al , 2019 ; Kim et al , 2019 ; Zou et al , 2019 ; Wang et al , 2019b ). Recent data indicated that high HMGCS2 expression caused reactive oxygen species (ROS) accumulation and loss of the mitochondrial membrane potential (MMP), which then induced diabetic cardiomyopathy (Wang et al , 2020a ). However, the exact role of HMGCS2 in renal fibrosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al showed that exercise training could reverse lipotoxicity-induced cardiomyopathy by repressing HMGCS2 [ 35 ]. Wang et al demonstrated that silencing of peroxisome proliferator-activated receptor-alpha alleviated myocardial injury in DCM by repressing HMGCS2 expression [ 39 ]. Sikder et al showed that circulating HMGCS2 was elevated in the high-fat diet-induced diabetic rats [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…DbCM is a common and severe complication of T1D with an increased incidence rate globally [ 1 , 2 , 29 ]. DbCM is manifested with diastolic function impairments and heart failure at the early stage, which contributes to the early morbidity and high mortality of T1D patients [ 30 , 31 ]. Multifactorial pathogenesis was observed in the progress of DbCM, such as metabolic disorders, autonomic dysfunction, abnormal homeostasis, interstitial fibrosis, and structural protein alteration [ 1 , 32 ].…”
Section: Discussionmentioning
confidence: 99%